Dystocia Due to a Monocephalus Tetrabrachius Tetrapus Dicaudatus Conjoined Monster in a Non-Descript Doe - bethapudi, srilatha; Mudiki, Phaneendra (The Indian Journal of Animal Reproduction, 2024)
Fetal anomalies and monstrosities are common cause of dystocia. The occurrence of foetal monstrosities often leads to difficulty in parturition and also failed to be delivered by traction. It is important to know various types of monsters which cannot be removed without Caesarean section. The present case report describes such type of monocephalus fetal monster having four forelimbs, four hind limbs and two tails which was successfully managed by caesarean section in a 4-year-old nondescript doe.